Value of electrophysiological indicators in differential diagnosis of parkinson's disease and multiple system atrophy - Wangwang Hu; Yifan Cheng; Jie Pan; Xun Wang; Shaojing Li; Zijian Fan; Bei Shao; Xiaoting Niu (BMC Neurology, 2023)
Abstract Background We evaluated the value of electrophysiological indicators by external anal sphincter electromyography (EAS-EMG), sympathetic skin response (SSR), R-R interval variation (RRIV), and Bulbocavernosus Reflex (BCR) in differential diagnosis of multiple system atrophy (MSA) and Parkinson’s disease (PD). Methods A total of 41 patients with MSA and 32 patients with PD were enrolled. The electrophysiological changes of autonomic dysfunction were assessed with BCR, EAS-EMG, SSR, and RRIV, and the abnormal rate of each indicator was calculated. The diagnostic value of each indicator was analyzed with ROC curve. Results The incidence rate of autonomic dysfunction in MSA group was significantly higher than that in PD group (p < 0.05). The abnormal rates of BCR and EAS-EMG indicators in MSA group were higher than those in PD group (p < 0.05). The abnormal rates of SSR and RRIV indicators in MSA group and PD group were high; however, there was no significant difference between MSA and PD groups (p > 0.05). The sensitivity of BCR combined with EAS-EMG indicators in differential diagnosis of MSA and PD were 92.3% in males and 86.7% in females, respectively, and the specificity was 72.7% in males and 90% in females, respectively. Conclusions Combined analysis of BCR and EAS-EMG has high sensitivity and specificity for differential diagnosis of MSA and PD.